Research trends on the quality of life in patients with metabolic dysfunction-associated fatty liver diseases: a scientific metrology study - Huang, Can; Chen, Meng; Sun, Yanfang; Zhang, Lin; Liu, Wei (Frontiers in Nutrition, 2025)
BackgroundMetabolic dysfunction-associated fatty liver disease (MAFLD) has become the most prevalent chronic liver disease globally, significantly impairing patients’ quality of life (QOL) through complex interactions with metabolic comorbidities, psychological factors, and disease progression. Despite growing research interest, a comprehensive bibliometric analysis of QOL studies in MAFLD remains lacking.MethodsPublications focusing on MAFLD and QOL were retrieved from the Web of Science Core Collection and Scopus. Bibliometric data, including titles, authors, institutions, countries, keywords, and citations, were extracted and analyzed using Bibliometrix (R-package) and VOSviewer. Annual publication trends, geographical contributions, institutional collaborations, journal influence, author networks, and keyword evolution were visualized.ResultsA total of 1,347 publications (2004–2025) were included, with an annual growth rate of 18.76%. The United States (n = 368, 27.3%) was the most productive country, followed by China (n = 171, 12.7%) and Italy (n = 94, 7.0%). Leading institutions included the University of California System (n = 67) and Harvard University (n = 54). Key journals included Hepatology (n = 27) and Journal of Hepatology (n = 15). Keyword analysis identified five clusters: obesity management, metabolic health, MAFLD pathology, health impacts, and risk factors. Emerging trends focused on drug therapy, lifestyle interventions, and psychosocial support.ConclusionResearch on MAFLD patients’ QOL is growing fast. Effective management needs integrated strategies (lifestyle, psychological support, multidisciplinary management, precision pharmacology) tailored to individuals. Future research should prioritize long-term data, clarity of mechanisms, and equitable interventions for patients’ holistic well-being.